Knowledge that binds - Chua, Khai Xin (Nanyang Technological University, 2023)
Knowledge That Binds is an investigation into the craft of bookbinding through the lens of a designer, to foster appreciation and encourage creatives to engage in the craft. Despite the decline of hand bookbinding, the craft is still relevant to creatives as it is frequently used in student projects and artist books in the art and design scene. This project seeks to study existing hand bookbinding techniques and aims to relook at hand bookbinding techniques for designers and artists who self-produce books and can benefit from hand bookbinding as a creative expression.